2019
DOI: 10.1109/tmag.2018.2890069
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Role of Coil Designs and Anatomical Variations in Cerebellar TMS

Abstract: Transcranial magnetic stimulation (TMS) is a non-invasive neuromodulation technique that is used for treating various neurological disorders such as major depressive disorder. TMS has been gaining popularity in the field of neurostimulation of the cerebellum, since the cerebellum is a complex structure connected with almost the entire central nervous system and TMS has promise for non-invasively probing cerebellar function. Recent studies have discovered that the cerebellum plays an important role not only in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…In summary, various studies have investigated inter-subject variability of the induced EF ranging from a few to up to 50 subjects (Bijsterbosch et differences (Opitz et al 2011, Bijsterbosch et al 2012, Janssen et al 2013. Also, the EF variability may be different according to the targeted brain part and population segment (Bijsterbosch et al 2012, Zhong et al 2019. In the studies reviewed in this and other subsections, adults have been the predominant population segment (figure 5(b)), and the elderly and youth populations are almost unexplored.…”
Section: Effects Of Anatomical and Inter-individual Factorsmentioning
confidence: 95%
See 2 more Smart Citations
“…In summary, various studies have investigated inter-subject variability of the induced EF ranging from a few to up to 50 subjects (Bijsterbosch et differences (Opitz et al 2011, Bijsterbosch et al 2012, Janssen et al 2013. Also, the EF variability may be different according to the targeted brain part and population segment (Bijsterbosch et al 2012, Zhong et al 2019. In the studies reviewed in this and other subsections, adults have been the predominant population segment (figure 5(b)), and the elderly and youth populations are almost unexplored.…”
Section: Effects Of Anatomical and Inter-individual Factorsmentioning
confidence: 95%
“…The variability was larger in other regions, which had complicated, variable, and distinct folding patterns between individuals. Zhong et al (2019) demonstrated the difference between two coils (conventional figureof-eight coil and the coil used for deep brain stimulation) targeting the cerebellum in 50 subjects using the FEM. The maximum induced EF strength had a normalised standard deviation ranging from 20 to 34% among subjects in the target regions.…”
Section: Effects Of Anatomical and Inter-individual Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…This model simplifies the material and geometric characteristics of a human head. A logical trend in rTMS modeling are so-called anatomically accurate models [15]. Commercially available anatomical models based on MRI image segmentation are especially popular today [16] [17] [18].…”
Section: Introductionmentioning
confidence: 99%
“…In computer modeling, a current of 5000 A is applied to TMS coils at a frequency of 2.5 kHz for output comparable to a conventional stimulator [55]. For coils with double windings (QBC, FOE coil, and their variant), the current direction in both windings is opposite to each other.…”
Section: Coil Modeling/computer Simulationsmentioning
confidence: 99%